Estimasi Risiko Pada Saham PT. Gojek Tokopedia Tbk dan Expected Shortfall Menggunakan ARIMA-GARCH Model - Amri, Ihsan Fathoni; Puspitasari, Linda; Priambodo, Danu; Azzahrani, Rahma Dewi; Haris, M. Al (Jambura Journal of Probability and Statistics, 2024)
Evaluation of losses is very important when investing in stocks where an approach is needed to take into account risk, the approaches that can be used are Value-at-Risk and Expected Shortfall. The purpose of this research is to estimate the Value-at-Risk and Expected Shortfall of PT. Gojek Tokopedia Tbk uses the time series model methodology. One year daily closing price of PT. Gojek Tokopedia Tbk will be used as a source of research data. During the time series modeling process, the ARIMA model is intended as an average model and the GARCH model for model volatility, both of which are used to predict stock movements. The average value and variance models are then intended to calculate the Value-at-Risk and Expected Shortfall of the stocks used, respectively. The results obtained for the VaR value were 0.088911 and the ES value was 0.122084. This shows that the ES method is superior in considering the risk of stock investment that has been analyzed.